Service Monitoring for a Mobile Money System - Correia, Diogo Manuel Santos (2020)
Mobile applications are gaining more and more market share and virtually everyone today has smartphones. This reality is no different in Africa, where the use of mobile payment systems has grown and allowed people without access to bank accounts to use their phones to perform banking operations. Currently, WIT Software provides these countries with a Mobile Money System solution providing a Backend and Mobile Application, that allows users to make and receive payments, lend money and pay into mortgages, check statements, and transactions’ history. Still, another important aspect is the availability and functionality so that users can use it without interruption. In this way, was proposed to design a monitoring platform that will allow users to perceive the health status of the total system from the users' side, to detect problems either in applications, servers or even in network components that may be running. Prevent the correct functioning of this system that allows millions of people to have their bank account associated with their mobile phone number. This report describes all the work carried out for nine months at the company WIT Software, which involves the design and implementation of a Monitoring Platform for a Mobile Payments System.